National level assessment of using existing airport infrastructures for photovoltaic deployment. (15th September 2021) - Jiang, Mingkun; Qi, Lingfei; Yu, Ziyi; Wu, Dadi; Si, Pengfei; Li, Peiran; Wei, Wendong; Yu, Xinhai; Yan, Jinyue
Highlights: The PV potential of China's 239 civil airports was evaluated. The airport PV in China is up to 2.5 GW with an annual output of 2.64 TWh. The power generation potential highly matches the energy demand at airports. Most airport PV systems can achieve a ROI of over 50% without any subsidy. The meaning of airport PV is discussed in the context of transport electrification. Abstract: The airport is one of the most fundamental infrastructures in our society, its terminal buildings and parking lots are ideal locations for photovoltaic (PV) installation. The future trend of the electrification of the aviation and automobile industries will increase the electricity demand at airports calls for the integration of PV systems with airport infrastructure. Understanding the benefits of airport PV systems is crucial for the stakeholders including investors, project developers and policymakers to promote PV sector development. Thus, evaluation of the PV potential and relevant economic performance of airports is essential. Combined with the geographic information system (GIS), the PV potential of the civil airports in China is investigated. The results show that potential PV capacity of China's 239 civil airports reaches up to 2.50 GW. The annual electricity demand of the aviation industry in 8 provinces can be self-satisfied via airport PV generation. Detailed economic analysis shows that all airport PV systems are profitable through appropriate investment and operation strategies.